Dewey : [large type] : the small-town library cat who touched the world - Myron, Vicki (Grand Central Publishing Large Print, 2008)
Traces the author's discovery of a half-frozen kitten in the drop-box of her small-community Iowa library and the feline's development into an affable library mascot whose intuitive nature prompted hundreds of abiding friendships, in a tale told against a backdrop of the town's struggles with the 1980s farm crisis.